Tetronace puelcha, argentine torpedo - Pollom, R. (2020)
The Argentine Torpedo (Tetronarce puelcha) is a medium-sized (to 120 cm total length) ray that occurs in the Southwest Atlantic from Espírito Santo, Brazil to San Jorge Gulf, Argentina. It is benthic on the continental shelf and slope at depths of 10–600 m, and also inhabits coastal lagoons. It is captured in intense and largely unmanaged commercial and artisanal demersal trawl and gillnet fisheries, which operate throughout most of its geographic range. Individuals that are caught are typically discarded at sea, but levels of post-release mortality are unknown. On the southern Brazilian shelf, this species declined by 97% in research trawl catch-per-unit-effort (CPUE) from 340 kg/hr in the 1980s to 10 kg/hr in 2005, equivalent to a >99% reduction over three generations. There are few data from Uruguay and Argentina, but this ray is rarely caught and may have undergone a similar decline there. Overall, due to the level of intense and inadequately managed fisheries throughout most of its range, its suspected unproductive life history, and significant estimated declines in CPUE in some areas, it is suspected that the Argentine Torpedo has undergone a population reduction of >80% over the past three generations (37.5 years), and it is assessed as Critically Endangered A2bd.